2016
DOI: 10.1177/1938640016685152
|View full text |Cite
|
Sign up to set email alerts
|

Is Incisura Fibularis a Reliable Landmark for Assessing Syndesmotic Stability? A Systematic Review of Morphometric Studies

Abstract: Anatomical, Level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…On the lateral aspect of the talocrural joint the syndesmosis is assessed for stability using tibiofibular clear space and tibiofibular overlap. These measurements unfortunately vary with gender, how the measurement was taken 26 and foot position. 27 There is no accepted consensus as to how this measurement should be taken.…”
Section: Preoperative Assessmentmentioning
confidence: 99%
“…On the lateral aspect of the talocrural joint the syndesmosis is assessed for stability using tibiofibular clear space and tibiofibular overlap. These measurements unfortunately vary with gender, how the measurement was taken 26 and foot position. 27 There is no accepted consensus as to how this measurement should be taken.…”
Section: Preoperative Assessmentmentioning
confidence: 99%
“…5,23,24,26,29,30,32 And of those reporting age, they exclusively involved elderly population. 25,27,28,31 This is of significance as various radiological and biomechanical studies have shown tibiofibular syndesmosis to be influenced by age 18,49 and gender. 18,49 Furthermore, variability observed in the current review may be attributable to the varied measurement tool used ranging from calipers 24,25,27,29 to 3-dimensional techniques, 28,31 varied measurement techniques, 29 and varied approaches in dissection.…”
Section: Discussionmentioning
confidence: 99%
“…25,27,28,31 This is of significance as various radiological and biomechanical studies have shown tibiofibular syndesmosis to be influenced by age 18,49 and gender. 18,49 Furthermore, variability observed in the current review may be attributable to the varied measurement tool used ranging from calipers 24,25,27,29 to 3-dimensional techniques, 28,31 varied measurement techniques, 29 and varied approaches in dissection. Finally, use of different landmarks for footprints like tibial articular surface 29 and superior border of the distal tibial articular cartilage, 31 rendered between study comparisons difficult.…”
Section: Discussionmentioning
confidence: 99%
“…FN is an important anatomical structure in the distal tibio bular syndesmosis, and there are extensive variations in the population [11,12]. Previous studies have con rmed that FN is a consistent index to evaluate the stability of syndesmotic [13][14][15]. Moreover, some anatomical con gurations of FN are related to the increased risk of speci c syndesmotic mal-reduction patterns, such as anteversion of the incisura correlated with anterior displacement of the bula, while retroversion of the incisura correlated with posterior bular displacement [16].…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies on the impact of gender differences on HAS, but a few studies report that the degree of injury in male is greater than that in female [2,21]. At the same time, the measurement of FN will be affected by gender, which may be due to the morphological differences between tibia and bula [15]. Therefore, based on the imaging data of axial CT, we analyzed the FN and HAS related to parameters of HAS patients of different genders the in uence of FN on HAS on the basis of excluding the anatomical differences caused by gender.…”
Section: Introductionmentioning
confidence: 99%